Conditions for building of language environment in higher educational institutions for nonlinguistic students’ intercultural and professional development - Shulgina, Elena M. (Вестник Томского государственного педагогического университета)
The purpose of the paper is to consider the key trends of the society transformation into a digital environment and the current conditions that the contemporary reality dictates. The contemporary environment determines the organizational changes within a modern university by searching for new mechanisms and methods for educational process managing when teaching a foreign language to non-linguistic students with an enhanced professional component that can promote forming a new infrastructure and consequently a new language environment via professional interpersonal communication. The research ambition is to explore the conditions for the formation and development of a new infrastructure within a multicultural educational environment; how this educational environment responds to newly emerging challenges and what makes us rethink the paradigm of the existing educational language environment in the university. Therefore, it follows that the concept of creating a new favorable intercultural educational environment is important for modern universities, particularly in a multilingual and multicultural university environment. The main task for finding mechanisms to manage the process of teaching a foreign language in a modern university is their subsequent transformation and, as a result, the formation and development of a new special language environment, which can be formed under specially created conditions in order to increase the efficiency, reliability and quality of professional education. Moreover, the formation of a language environment within the university context in the process of teaching a professional foreign language to non-linguistic students on a new basis allows us to change the logic of learning processes. It makes us to move to new forms of learning, including online learning, based on the introduction of digital technologies, taking into account personal and professional development and interdisciplinary features. In the paper, the authors propose to consider the conditions for the development of a favorable educational environment within the concept of “Big University”, where the key element is the linguodidactic urban environment with active language practice. There is an assumption that the digital transformation, taking place in education as part of a change in the philosophy of foreign language teaching will somehow increase the professional component of students, including their skills and abilities, due to accessibility with the help of the use of professional interpersonal communication within a foreign language urban environment. The paper provides a number of examples of successful projects that encourage attracting both domestic experts, including the current faculty, and foreign professors as well as students of bachelor’s, master’s, and postgraduate degrees.